James Monroe : a Republican champion - Poston, Brook Carl (Contested boundaries., 2019)
This work examines James Monroe's attempt to craft a legacy as a champion of American republicanism. Monroe wanted to make the U.S. a beacon of republicanism around the world and secure his place as the republic's greatest diplomat.